Adenoviruses using the cancer marker EphA2 as a receptor in vitro and in vivo by genetic ligand insertion into different capsid scaffolds. - Michael Behr; Johanna K Kaufmann; Patrick Ketzer; Sarah Engelhardt; Martin Mück-Häusl; Pamela M Okun; Gabriele Petersen; Frank Neipel; Jessica C Hassel; Anja Ehrhardt; Alexander H Enk; Dirk M Nettelbeck (PLoS ONE, 2014)
Adenoviral gene therapy and oncolysis would critically benefit from targeted cell entry by genetically modified capsids. This requires both the ablation of native adenovirus tropism and the identification of ligands that remain functional in virus context. Here, we establish cell type-specific entry of HAdV-5-based vectors by genetic ligand insertion into a chimeric fiber with shaft and knob domains of the short HAdV-41 fiber (Ad5T/41sSK). This fiber format was reported to ablate transduction in vitro and biodistribution to the liver in vivo. We show that the YSA peptide, binding to the pan-cancer marker EphA2, can be inserted into three positions of the chimeric fiber, resulting in strong transduction of EphA2-positive but not EphA2-negative cells of human melanoma biopsies and of tumor xenografts after intratumoral injection. Transduction was blocked by soluble YSA peptide and restored for EphA2-negative cells after recombinant EphA2 expression. The YSA peptide could also be inserted into three positions of a CAR binding-ablated HAdV-5 fiber enabling specific transduction; however, the Ad5T/41sSK format was superior in vivo. In conclusion, we establish an adenovirus capsid facilitating functional insertion of targeting peptides and a novel adenovirus using the tumor marker EphA2 as receptor with high potential for cancer gene therapy and viral oncolysis.